Retracted: Econometric modeling and forecasting of environmental conditions of cities and population health problems: Case study of Navoi and Zarafshan cities - Latipov, Normurod; Komilova, Nilufar; Makhmudov, Bakhodirjon; Berdiev, Khayriddin; Moslemzadeh, Mehrdad; Chulliyev, Suhrob; Murtazayev, Isabek; Hamroyev, Mukhtor (Macedonian Journal of Ecology and Environment, 2024)
In this research work, the problems of connection between various harmful substances emitted into the atmosphere and population morbidity indicators were analyzed in Navoi and Zarafshan, two important cities of the Navoi region, located in the industrialized and arid climate region of the Republic of Uzbekistan, located in the Central Asian region. The obtained results show that in the city of Navoi, there is a high correlation between diseases related to the respiratory system, diseases of the blood and blood-forming organs and immune system, diseases of the nervous system, and annual harmful substances released into the atmosphere. In the city of Zarafshan, there is a strong direct connection between the harmful substances released into the atmosphere and diseases related to the digestive organs, that is, the increase or decrease of various harmful substances in a certain amount, as mentioned above It can also increase or decrease the mentioned diseases. In conclusion, there is a direct correlation between the environmental conditions of industrialized and arid climate regions and the issues of public health, and the increase or decrease of one affects the trend of the other directly. It is more important than ever to develop the necessary measures with a proper understanding of this causal effect. Taking into account all the above points, we have developed some suggestions and recommendations.